Utilization of waste coir fibre architecture to synthesize porous graphene oxide and their derivatives: An efficient energy storage material. (10th December 2020) - Yadav, Krishna K.; Singh, Harish; Rana, Supriya; Sunaina,; Sammi, Heena; Nishanthi, S.T.; Wadhwa, Ritika; Khan, Nausad; Jha, Menaka
Abstract: Now-a-day's lot of researcher interest is directed towards the conversion of bioresources (waste) to carbon-based materials for meeting the demand of sustainable energy. In the present study, we have utilized waste coir fibres for the synthesis of graphene oxide and its derivatives. Microscopic investigation of coir fibre indicates that silica microspheres assembled in a regular pattern inside the cellulose matrix of coir fibre. Here, we have attempted to make water-soluble silica-based compound via reaction of coir with alkali metal hydroxide. Further, heating of water-soluble silicates-cellulose mixture leads to the formation of porous graphene oxide having high specific surface area (1114 m 2 /g). Doping of sulphur and nitrogen has been done via the chemical route, which leads to enhancement in electronic conductivity. The electrochemical study of bare and doped graphene oxide have been carried out using electrochemical work station. The electrochemical study confirms that nitrogen-doped graphene oxide has highest specific capacitance (278.6 F/g) as compared to bare graphene oxide (166.1 F/g) and sulphur doped graphene oxide (199.2 F/g) at 1 A/g discharge current because of high charge carrier density in nitrogen-doped graphene oxide (9.7 × 10 14  cm −3 ). The galvanic charge-discharge (GCD) stability shows ∼82% capacitance retention after 2000 GCD cycle at 3 A/g of nitrogen-doped graphene. The above approach for conversion of low-value coir fibre to high-value energy storage material (graphene oxide) would certainly be interest of the researchers working in the field of energy storage, environmental pollution control, waste management, materials science, sustainable chemistry and engineering for achieving the goal of cleaner production technologies for better environmental sustainability. Graphical abstract: Image 1 Highlights: Investigation of coir fibre microstructure using an electron microscopy technique. Design of chemical process to convert coir fibre into porous graphene oxide. Sulphur/Nitrogen being doped for increasing the conductivity of graphene oxide. N-doped graphene shows the highest specific capacity (278.6 F/g at 1 A/g).